Measurement of Degree of Compaction of Fine-Grained Soil Subgrade Using Light Dynamic Penetrometer - Junhui Zhang; Yongsheng Yao; Jianlong Zheng; Xiangqun Huang; Tian Lan (Advances in Civil Engineering)
To determine the degree of compaction of subgrades filled with fine-grained soil, the compaction test and light dynamic penetrometer (LDP) test were carried out for low liquid-limit clay samples with different water contents in laboratory. Then, a prediction equation of the penetration ratio (PR) defined as the depth per drop of the hammer of LDP, degree of compaction (K), and water content (ω) was built. After that, the existing fine-grained soil subgrades on LDP-based field tests were excavated. The on-site PR values, water contents, and degrees of compaction of slopes were obtained. The estimated degrees of compaction using the prediction equation were compared with measured values of the degree of compaction in field. The results show that there is good consistency between them, and an error within 3.5% was obtained. In addition, the water content should be determined firstly while using the prediction equation which is proposed in this study. Therefore, a numerical method of the water content of a subgrade was developed, and the predicted and measured water contents were compared, which shows a relatively high relativity. Then, the degree of compaction of fine-grained soil subgrades can be calculated according to the predicting equation, which involves the penetration ratio (PR) and the numerically calculated water content as input instead of the measured value in the field.